“The Huns and Vandals are thundering at our gates and within our gates”: Faces of the Enemy in Saskatoon during the Second World War - Kelly, Brendan (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2011)
Although at a safe remove from combat during the Second World War, many citizens of Saskatoon exhibited a strange sense of embattlement. During these years fearful residents believed the city to be under threat by a succession of enemies, including German Canadians, Hitler’s Wehrmacht, Japanese Canadians, communists, and the provincial Co-operative Commonwealth Federation. Which foe occupied the spotlight shifted with time and the changing fortunes of war. Come the summer of 1944, enemies that had seemed so real during the early years of the war had all but vanished. By D-Day and the June provincial election, Saskatonians had overcome their wartime paranoia and optimistically turned their attention towards the more pressing needs of domestic reconstruction.